A NEW SPECIES OF HEDYOTIS (RUBIACEAE) FROM INDIA. (24th February 2014) - Karuppusamy, S.; Ravichandran, V.
<x content-type="archive" xml:space="preserve">Abstract</x> A new species, Hedyotis rajasekaranii Karupp. & Ravichandran (Rubiaceae), is described from the Megamalai Hills of the Western Ghats in Tamil Nadu, southern India.